Optimization of the nanotwin-induced zigzag surface of copper by electromigration. Issue 5 (20th January 2016) - Chen, Hsin-Ping; Huang, Chun-Wei; Wang, Chun-Wen; Wu, Wen-Wei; Liao, Chien-Neng; Chen, Lih-Juann; Tu, King-Ning
Abstract : By adding nanotwins to Cu, the surface electromigration (EM) slows down. Abstract : By adding nanotwins to Cu, the surface electromigration (EM) slows down. The atomic mobility of the surface step-edges is retarded by the triple points where a twin meets a free surface to form a zigzag-type surface. We observed that EM can alter the zigzag surface structure to optimize the reduction of EM, according to Le Chatelier's principle. Statistically, the optimal alternation is to change an arbitrary (111)/( hkl ) zigzag pair to a pair having a very low index ( hkl ) plane, especially the (200) plane. Using in situ ultrahigh vacuum and high-resolution transmission electron microscopy, we examined the effects of different zigzag surfaces on the rate of EM. The calculated rate of surface EM can be decreased by a factor of ten.